Monomer Recovery and Nano-Silica Separation From Biodegraded Waste Silicone Rubber Shed of Composite Insulator - Yang, Shifang; Liu, Yunpeng; Zhou, Dasen (Frontiers in Materials, 2022)
Composite insulators are widely used in the external insulation of transmission lines due to their excellent pollution flashover resistance. However, the large amount of silicone rubber material is difficult to degrade naturally in decommissioned composite insulators resulting in great pressure on the environment. A method for recycling waste silicone rubber by microbial degradation was proposed. The insulator shed materials of composite insulators naturally retired under 10-15 years of operation are collected. Using dominant species to decompose silicone rubber, the decomposed product is obtained, and the chemical reaction process is deduced according to the three-dimensional structural characteristics of monomers. The biodegradation process does not require the participation of strong acid and alkali, and the recovery method is safe and effective. At the same time, the nano-silicon dioxide is separated from waste silicone rubber and modified by the surfactant. The particle size of nano-silica is reduced to ~18 nm with an excellent dispersibility, indicating a high economic value. It is demonstrated that microbial decomposition recycles polymeric materials with the ability to turn them into a valuable resource, which is a very low-carbon green and environmentally friendly method of recycling.